A Novel Methodology of Using Nonsolvent in Achieving Ultraclean Transferred Monolayer MoS2. Issue 13 (23rd March 2022) - Bhuyan, C. Abinash; Madapu, Kishore K.; Prabakar, K.; Das, Arindam; Polaki, S. R.; Sinha, Shyam K.; Dhara, Sandip
Abstract: The transfer of monolayer molybdenum disulfide (1L‐MoS2 ) onto any target substrates is inevitable for the next generation of optoelectronic devices such as flexible electronics. However, the existing post‐transfer treatments are ineffective for the complete removal of poly(methyl methacrylate) (PMMA) polymer, which is usually used as carrier polymer in the wet‐transfer method. The presence of PMMA residues seriously degrades the intrinsic properties of any 2D materials. Several new cleaning methods such as annealing, ozone cleaning, and acetone treatment adopted in this report are found to be ineffective for the complete removal of PMMA residues on the transferred 1L‐MoS2 film. A new chemical route is developed and demonstrated with a PMMA nonsolvent, ethanol, and ultraclean transferred 1L‐MoS2 is obtained after 96 h hot ethanol treatment. An interfacial diffusion model is proposed for the mechanism of PMMA removal from the 1L‐MoS2 surface. To observe the effect of cleaning process on electrical properties, 1L‐MoS2 field‐effect transistor (FET) devices are fabricated. An enhancement of 80%–85% in the electron mobility is achieved for ultraclean 1L‐MoS2 . One order improvement in the FET parameters such as ON/OFF ratio and the subthreshold slope is also observed. It is believed that this novel method can also be applicable for other 2D materials. Abstract : Several new cleaning methods such as ozone cleaning, annealing, and acetone treatment are found to be ineffective for the complete removal of poly(methyl methacrylate) (PMMA) residues from wet‐transferred monolayer MoS2 . In this context, a simple yet effective chemical treatment, 96 h of hot ethanol cleaning, is found to remove the PMMA residues completely. The ultraclean monolayer MoS2 has shown improved field‐effect transistor performance.